Combined Effect of Age and Baseline Alberta Stroke Program Early Computed Tomography Score on Post-Thrombectomy Clinical Outcomes in the MR CLEAN Registry. Issue 12 (December 2020) - Ospel, Johanna; Kappelhof, Manon; Groot, Adrien E.; LeCouffe, Natalie E.; Coutinho, Jonathan M.; Yoo, Albert J.; Yo, Lonneke S.F.; Beenen, Ludo F.M.; van Zwam, Wim H.; van der Lugt, Aad; Postma, Alida A.; Roos, Yvo B.W.E.M.; et al.
Abstract : Background and Purpose: Ischemic brain tissue damage in patients with acute ischemic stroke, as measured by the Alberta Stroke Program Early CT Score (ASPECTS) may be more impactful in older than in younger patients, although this has not been studied. We aimed to investigate a possible interaction effect between age and ASPECTS on functional outcome in acute ischemic stroke patients undergoing endovascular treatment, and compared reperfusion benefit across age and ASPECTS subgroups. Methods: Patients with ischemic stroke from the MR CLEAN Registry (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands; March 2014–November 2017) were included. Multivariable ordinal logistic regression was performed to obtain effect size estimates (adjusted common odds ratio) on functional outcome (modified Rankin Scale score) for continuous age and granular ASPECTS, with a 2-way multiplicative interaction term (age×ASPECTS). Outcomes in four patient subgroups based on age (< versus ≥ median age [71.8 years]) and baseline ASPECTS (6–10 versus 0–5) were assessed. Results: We included 3279 patients. There was no interaction between age and ASPECTS on modified Rankin Scale ( P =0.925). The highest proportion of modified Rankin Scale 5 to 6 was observed in patients >71.8 years with baseline ASPECTS 0 to 5 (68/107, 63.6%). There was benefit of reperfusion in all age-ASPECTS subgroups. Although the adjusted common odds ratio was lower in patients >71.8 years with ASPECTS 0 to 5 (adjusted common odds ratio, 1.60 [95% CI, 0.66–3.88], n=110), there was no significant difference from the main effect ( P =0.299). Conclusions: Although the proportion of poor outcomes following endovascular treatment was highest in older patients with low baseline ASPECTS, outcomes did not significantly differ from the main effect. These results do not support withholding endovascular treatment based n a combination of high age and low ASPECTS. Abstract : Supplemental Digital Content is available in the text.